2004
DOI: 10.1007/s10654-004-5758-6
|View full text |Cite
|
Sign up to set email alerts
|

Choosing immunisation coverage indicators at the local level

Abstract: Parental recall and data from cards are comparable sources, but the former is more sensitive than the latter in retrospective studies. Verbal recall should be accepted as reasonably reliable in the absence of cards. Age-appropriate indicators give a more complete evaluation of the susceptibility in the population, and are more precise at the local level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Some authors from developed countries have suggested that maternal recall is not a good enough indicator of vaccination status compared with health facility records [20,21]. However, a study from Italy found that parental recall alone was similar to other measures of vaccination status and concluded that "verbal recall should be accepted as reasonably reliable in the absence of cards" [22], while in Australia parental recall of measles vaccination coincided as well as vaccination cards with the presence of antibodies [23]. A study in Turkey, taking polio antibodies as the 'gold standard', found that parental recall was more sensitive but less specific than official records [24].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors from developed countries have suggested that maternal recall is not a good enough indicator of vaccination status compared with health facility records [20,21]. However, a study from Italy found that parental recall alone was similar to other measures of vaccination status and concluded that "verbal recall should be accepted as reasonably reliable in the absence of cards" [22], while in Australia parental recall of measles vaccination coincided as well as vaccination cards with the presence of antibodies [23]. A study in Turkey, taking polio antibodies as the 'gold standard', found that parental recall was more sensitive but less specific than official records [24].…”
Section: Discussionmentioning
confidence: 99%
“…Vaccine coverage is the most frequently used indicator of immunization among children between 12 and 23 months of age, but delays in delivery are overlooked (Chu et al [20]; Faustini et al [30]; Hull et al [33]; Akmatov et al [4]). Vaccines have the highest effectiveness during the recommended age range, and yet show lower compliance than uptake rates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many studies have shown that reported and recorded vaccination history data are fraught with biases and errors in recall and omission [4,6,8,11,16,36,37]. Studies in Bangladesh [38], Costa Rica [9], and England [39] found that maternal report inflated coverage estimates but our results illustrated that maternal report or card + history indicators performed well compared to serological and government estimates of MCV1 coverage.…”
Section: Discussionmentioning
confidence: 47%